Визначення параметрів системи випромінювання для лікування хвороб великої рогатої худоби - Попрядухін, Вадим Сергійович; Попрядухин, Вадим Сергеевич; Popriadukhin, Vadym; Попова, Ірина Олексіївна; Попова, Ирина Алексеевна; Popova, Iryna (ТДАТУ, 2020)
UK: Терапевтична ефективність використання лікувальних засобів для лікування хвороб і розладів функцій гонад корів доволі низька. Крім того не враховуються негативні дії на людину антибіотиків та інших медикаментів, що потрапляють через молоко і м'ясо корів і пригнічують імунітет, вражають печінку та інші органи. Тому немедикоментозне лікування гонад у корів за допомогою інформаційного електромагнітного поля є більш перспективним. В роботі проведено аналітичне обґрунтування параметрів і діаграми направленості рупорохвилеводної системи для лікування корів. Прийнята випромінююча система з обтічником, що має пірамідальний рупор, який переходить у прямокутний хвилевід чотирьох міліметрового діапазону. Визначені параметри головних пелюстків діаграми спрямованості і рівень потужності при частоті на поверхні, прямокутного розкриву, розмірів прямокутного розкриття, розмірів хвилевода, діаметр, товщина і фокусна відстань діелектричної лінзи дозволяють розробити пристрій для опромінення гонад корів. RU: Терапевтическая эффективность использования лекарственных средств для лечения болезней и расстройств функций гонад коров довольно низкая. Кроме того, не учитываются негативные воздействия на человека антибиотиков и других медикаментов, попадают через молоко и мясо коров, которые подавляют иммунитет, поражают печень и другие органы. Поэтому не медикаментозное лечения гонад у коров с помощью информационного электромагнитного поля является более перспективным. В работе проведено аналитическое обоснование параметров и диаграммы направленности рупорной волновой системы для лечения коров. Принятая излучающая система с обтекателем, имеет пирамидальный рупор, который переходит в прямоугольный волновод четырехмиллиметрового диапазона. Определены параметры головки лепестка диаграммы направленности и уровень мощности при частоте на поверхности, прямоугольного раскрытия, размеры прямоугольного раскрытия, размеры волновода, диаметр, толщина и фокусное расстояние диэлектрической линзы, это позволяет разработать устройство для облучения гонад коров. EN: The therapeutic efficiency of the use of drugs for the treatment of diseases and disorders of the functions of the gonads of cows is rather low, since the complex multicomponent complex in the regulation of sexual function, the dynamics of the state of hormonal receptors and the sensitivity of the corresponding organs of cows are not taken into account. In addition, the negative effects on humans of antibiotics and other medications are not taken into account, they enter through milk and cow meat, which suppress the immune system, affect the liver and other organs. Therefore, non-drug treatment of gonads in cows using an electromagnetic information field is more promising. The paper provides an analytical substantiation of the parameters and directional patterns of the horn wave system for the treatment of cows. The adopted radiating system with a fairing has a pyramidal horn that transforms into a rectangular waveguide of four millimeter wavelengths. The whole structure is located in a dielectric vinyl plastic tube. For centering the waveguide elements in the pipe, foam inserts are used. Emitters of this type provide an axially symmetrical and narrow radiation pattern. To calculate the parameters of the irradiation system, the aperture method was used; it is assumed that the size of the opening of the system is much larger than the wavelength. On the basis of the anatomical construction of cow gonads, for repeated intrauterine irradiation of the reproductive organs of cows, the geometric dimensions of the irradiation system, the density and dielectric constant of the material, and the dielectric loss tangent of the fairing were determined. The parameters of the lobe head and the power level at the surface frequency, rectangular opening, the dimensions of the rectangular opening, the dimensions of the waveguide, the diameter, thickness and focal length of the dielectric lens have been determined; this makes it possible to develop a device for irradiating the gonads of cows.
Определение параметров системы излучения для лечения болезней крупного рогатого скота
Determination of parameters of radiation systems for treatment of diseases of diseases of cattle
Keywords: інформаційне електромагнітне поле; міліметрові хвилі; внутрішньоутробне лікування; патогенні коки; информационное электромагнитное поле; миллиметровые волны; внутриутробное лечение; патогенные кокки; informational electromagnetic field; millimeter waves; intrauterine treatment; pathogenic cocci